Representations of public caning in Serambi Indonesia: A linguistic approach to news framing analysis - Febri Nurrahmi; Nasya Bahfen (Studies in English Language and Education, 2024)
With its distinctive autonomy in implementing Sharia, Aceh allows public caning as a form of corporal punishment not seen in other parts of Indonesia. This article examines how a prominent local newspaper, Serambi Indonesia, portrayed the implementation of public caning in Aceh over the past decade. This study combined transivity analysis and Gamson and Modiglianis (1989) four framing devices: metaphors, exemplars, catchphrases, and depictions. The analysis focused on 45 articles related to public caning in Aceh published between January 2012 and December 2020 in Serambi Indonesia. The findings reveal that caning is a key theme in these news stories, signalling its execution for Sharia violators in Aceh. The findings also found an ambivalent representation of public caning. Depictions of paramedics, audiences, and public support, along with the use of exemplars, highlight a positive portrayal of the current practice of public caning in Aceh. The punishment is depicted as a way of educating offenders and a means to deter similar offenses in the future, which overshadows the severity of the punishment. The media also conveys a message that Acehs caning punishment differs from practices in the Middle East and suggests a lighter interpretation of Sharia. However, the coverage raises concerns about the effectiveness of caning as a deterrent and the fair implementation of the punishment. Therefore, the representations of public caning in Serambi Indonesia reflects ongoing controversy surrounding the event within Acehnese society.